1965
DOI: 10.1111/j.1570-7458.1965.tb00861.x
|View full text |Cite
|
Sign up to set email alerts
|

OBSERVATIONS ON THE CONTROL OF TETRANYCHUS URTICAE KOCH ON CUCUMBERS BY THE PREDATORY MITE PHYTOSEIULUS RIEGELI DOSSE

Abstract: The interaction between Tetranychus urticae and Phytoseiulus riegeli on cucumbers was studied in several different experiments at two centres. It was shown that if the predator is introduced at a low prey population, elimination of the mites occurred before leaf‐injury became sufficiently high to cause a reduction in cucumber yield. A theoretical pattern of mite control and leaf‐damage is discussed, and it is concluded that economic control should follow two introductions of Phytoseiulus during the first 25 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

1971
1971
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 5 publications
0
35
0
2
Order By: Relevance
“…Further experiments have to be done to determine whether the total crop damage of three or two pest species is less than the damage inflicted by one of the pest species. Releasing pest species in a crop is considered risky, but is accepted in some cases, such as in sweet pepper, where some growers use the ''pest-in-first'' strategy with spider mites to enhance control by P. persimilis (Hussey et al 1965; K. Bolckmans, R&D Department, Koppert BV, personal communication). Avoiding total eradication of all pest species, thereby maintaining some pest diversity, might be more acceptable for the growers than introducing a new pest.…”
Section: Discussionmentioning
confidence: 99%
“…Further experiments have to be done to determine whether the total crop damage of three or two pest species is less than the damage inflicted by one of the pest species. Releasing pest species in a crop is considered risky, but is accepted in some cases, such as in sweet pepper, where some growers use the ''pest-in-first'' strategy with spider mites to enhance control by P. persimilis (Hussey et al 1965; K. Bolckmans, R&D Department, Koppert BV, personal communication). Avoiding total eradication of all pest species, thereby maintaining some pest diversity, might be more acceptable for the growers than introducing a new pest.…”
Section: Discussionmentioning
confidence: 99%
“…Phytoseiid mites have been shown to be effective in controlling tetranychids in a variety of situations, most notably those in greenhouses (Chant, 1961;Hussey and Parr, 1965;Gould et aL, 1969;Dixon, 1973;Markkula and Tiitanen, 1976), strawberry (Oatman, 1965;Oatman and McMurtry, 1966;Oatman et al, 1968), and deciduous fruit (Putman and Herne, 1964;1966). Huffaker et al (1970) discuss at length the functional, numerical and total responses of phytoseiid predators and their respective importance in prey regulation.…”
Section: Introductionmentioning
confidence: 98%
“…Pesticide resistance in T. urticae has promoted biological control techniques based on the use of Phytoseiulus persimilis Athias-Henriot. The effectiveness of this predator in controlling T. urticae in greenhouse cucumbers was shown in the early 1960s (Chant 1961;Bravenboer and Dosse 1962;Hussey et al 1965). Later, it was reported that low relative humidity and high temperatures affect P. persimilis performance in controlling T. urticae (Force 1967;Stenseth 1979;El-Laithy 1996).…”
Section: Introductionmentioning
confidence: 93%